2014
DOI: 10.1080/13636820.2014.922119
|View full text |Cite
|
Sign up to set email alerts
|

The role of collaborative learning on training and development practices within the Australian Men’s Shed movement: a study of five Men’s Sheds

Abstract: This study examines the role and impact of collaborative learning on training and development practices in Australian Men's Sheds. We use a case study approach, underpinned by Peters and Armstrong's theoretical framework of collaborative learning in adult education, to investigate five Men's Sheds. Semi-structured interviews were carried out with five Men's Shed co-ordinators, and five focus groups with a total of 61 members. In this study, vocational education and training is extended in a way to bridge the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…The organisation introduced HPWS with the aim of improving performance and achieved this through integrating HRM with traditional and religious values that guided the organisation. Moreover, in the case of volunteer and grassroots community organisations, the formalisation of management practices and process may be detrimental to the attraction and retention of volunteers (Cavanagh, Southcombe, & Bartram, 2014;Cavanagh et al, 2013). Volunteers may hold negative views of formalisation of their volunteering experience in that formalisation may be perceived as bureaucratic and similar to paid work.…”
Section: Key Emergent Themes and Thoughts For Future Researchmentioning
confidence: 99%
“…The organisation introduced HPWS with the aim of improving performance and achieved this through integrating HRM with traditional and religious values that guided the organisation. Moreover, in the case of volunteer and grassroots community organisations, the formalisation of management practices and process may be detrimental to the attraction and retention of volunteers (Cavanagh, Southcombe, & Bartram, 2014;Cavanagh et al, 2013). Volunteers may hold negative views of formalisation of their volunteering experience in that formalisation may be perceived as bureaucratic and similar to paid work.…”
Section: Key Emergent Themes and Thoughts For Future Researchmentioning
confidence: 99%
“…Members had previously been employed in manual skilled, managerial and professional roles, and engaged in community volunteering . Activities and services provided to members and community through this Men's Shed resembled those delivered in Men's Sheds elsewhere . The majority (80%) of Men's Shed members were also members of other groups, clubs or organisations.…”
Section: Discussionmentioning
confidence: 99%
“…2 Activities and services provided to members and community through this Men's Shed resembled those delivered in Men's Sheds elsewhere. 2,[6][7][8][9][22][23][24] The majority (80%) of Men's Shed members were also members of other groups, clubs or organisations. This finding is higher than research by Golding et al (2007) who found 50% of members of Victorian Men's Sheds were members of other clubs.…”
Section: Discussionmentioning
confidence: 99%
“…Over recent decades, Men's Sheds have emerged as grassroots community-based organisations for mainly older and retired men to participate together in various workshop and social activities. Men's Sheds are now entrenched within the Australian cultural landscape with more than 100,000 members utilising nearly 1,000 Sheds registered on a regular basis (Cavanagh et al ., 2014; Australian Men's Shed Association (AMSA), 2017). Internationally, Men's Sheds are present in New Zealand, the United Kingdom, Ireland, Europe, Canada and the United States of America (Southcombe et al ., 2015; Nurmi et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%